2012
DOI: 10.1029/2011gl050606
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity of ultra‐oligotrophic marine ecosystems to atmospheric nitrogen deposition

Abstract: [1] Using a model of plankton and organic-matter cycling we demonstrate that variable stoichiometric ratios can lead to a more than 5-fold higher sensitivity of simulated carbon export to atmospheric N deposition in the ultra-oligotrophic eastern part of the North Atlantic subtropical gyre compared to the westerly oligotrophic region near Bermuda, often used as a reference site for subtropical regions. Stronger nutrient limitation in the ultra-oligotrophic east causes higher phytoplankton C:N ratios and lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The higher C : N ratio computed for ESTOC was consistent with the carbon rich organic matter observed in the mixed layer (Koeve, 2006) and the sinking organic matter in the region, and with close to Redfield ratios observed in the sinking organic matter at BATS (Schnetzer and Steinberg, 2002). Moreover, ecological models employed to study the sensitivity of carbon export to atmospheric nitrogen inputs in NASW and NASE showed higher C : N values in the sinking organic matter in NASE (Mouriño-Carballido et al, 2012).…”
Section: Remineralization Ratessupporting
confidence: 83%
See 1 more Smart Citation
“…The higher C : N ratio computed for ESTOC was consistent with the carbon rich organic matter observed in the mixed layer (Koeve, 2006) and the sinking organic matter in the region, and with close to Redfield ratios observed in the sinking organic matter at BATS (Schnetzer and Steinberg, 2002). Moreover, ecological models employed to study the sensitivity of carbon export to atmospheric nitrogen inputs in NASW and NASE showed higher C : N values in the sinking organic matter in NASE (Mouriño-Carballido et al, 2012).…”
Section: Remineralization Ratessupporting
confidence: 83%
“…Another source of new nitrogen that could explain the observed differences in carbon export between the two stations is biological nitrogen fixation. Recent studies indicate that this process supplies a significative contribution to total new nitrogen inputs in oligotrophic waters (Capone et al, 2005;Mouriño-Carballido et al, 2011;Bonnet et al, 2011). Biogeochemical estimates suggest a lower contribution of nitrogen fixation at ESTOC compared with BATS (Neuer et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Had we considered variable stoichiometry there, the very low N:C ratio of phytoplankton would cause a much higher NPP response compared to what we simulated with our fixed stoichiometry model. Mouriño‐Carballido et al [] showed that this effect can lead to an up to fivefold higher response of NPP, but only where nitrate is more or less permanently low. Such a larger fertilization would induce a stronger thermocline deoxygenation and hence a stronger response of the stabilizing feedback via denitrification.…”
Section: Caveatsmentioning
confidence: 99%
“…In this work, the abilities of the ACCMIP MMM (Lamarque et al, 2013a) and the TM4-ECPL model, hereafter TM4 (Kanakidou et al, 2016;Myriokefalitakis et al, 2015), to estimate atmospheric N dry deposition to the ocean are evaluated. The evaluation was done by comparison to a substantial database of aerosol N observations collected during ships' voyages over all the major ocean basins.…”
Section: Introductionmentioning
confidence: 99%